Factors Affecting Academic Stress in Medical Students Literature Review - Nirwan, Qurratul Aini; Rahmanisa, Soraya; Daulay, Suryani Agustina; Sari, Ratna Dewi Puspita (CV. Jasa Sukses Abadi, 2025)
A student is an individual who studies at a higher education institution. A medical student is a student who requires dedication and undergoes significant pressure to complete their studies. Medical students are highly vulnerable to academic stress. Stress is a threatening state experienced by an individual, while a stressor is the source of stress. Academic stress occurs when students face academic pressure, such as intensive learning activities. Stressors that can contribute to academic stress include exams, practical sessions, assignments, and time constraints that must be managed within a short period. Academic stress impacts mental health, which in turn affects students' academic performance. Stress induced by psychological pressure causes changes in the body, resulting in two types of responses: slow and fast responses. These responses are linked to two physiological systems: the sympathetic adrenomedullary system and the hypothalamic-pituitary-adrenal HPA axis. Several factors influence academic stress in medical students, including self-efficacy, hardiness, optimism, achievement motivation, procrastination, and social support. High self-efficacy helps students manage stress, while hardiness strengthens their resilience in facing pressure. Optimism and achievement motivation contribute to students' ability to recover from failure and stay focused on their goals. Conversely, procrastination worsens stress due to delays in completing tasks. Social support from family, friends, and institutions plays a crucial role in reducing stress by providing a sense of security and emotional balance for students.